SÍNDROME DO CLIMATÉRIO: inquérito populacional domiciliar em São Luís, MA - Malheiros, Elizabeth Santos de Andrade (2010)
The climacterium is the period of a woman's life that marks the transition from reproductive stage and non reproductive stage, resulting from the gradual decline of ovarian function and the occurrence of menopause. It is marked by changes in the female body, such as vasomotor symptoms, psychological, genitourinary, sexual and sleep disturbance. The aim of this study was to evaluate the prevalence of climacteric symptoms. This is a descriptive and cross-sectional population-based study. It enrolled 1210 perimenopausal women from 45 to 60 years old. Interviews were conducted by a specific questionnaires in the period from April to July 2008. Data analysis was performed by chi-squared test and Kruskal-Wallis variance. The intensity of climacteric symptoms was analyzed by circulatory and psychological index. The mean age of natural menopause was 48 years (SD ± 4.61), and the minimum age was 25 and maximum was 58 years. The prevalence of symptoms associated with the climacteric syndrome was 77,8%, especially hot flashes and sweating that was most prevalent vasomotor symptoms. Nervousness and irritability were most frequent psychological disturb. The intensity of vasomotor symptoms and psychological, calculated by circulatory and psychological index, do not have a significant differences according to menopausal stage. There was a prevalence of vaginal dryness as the most prevalent genitourinary complaint. It was observed that most menopausal women of São Luis is in the age group of 55-60 years, brown color, with 09 to 11 years of schooling, married, with gainfully employed, Catholic and from social class C. This study concluded that the prevalence of climacteric symptoms was high in climacteric women living in São Luis, especially: hot flashes, sweating, nervousness, irritability, vaginal dryness and dyspareunia. The intensity of vasomotor and psychological symptoms was significantly higher in peri and postmenopause